The effectiveness of solution-focused brief counseling in reducing bullying behavior - Yeschisca, Bettrisca Zefilla; Suardiman, Siti Partini; Supriyanto, Agus (Journal of Professional Teacher Education, 2023)
Bullying is a problem that until now requires intensive handling from several parties, one of which is the implementation of Guidance and Counseling services. A strategy counselors can use to deal with the problem of bullying is brief, solution-focused counseling. This study aims to determine the effectiveness of concise counseling focused on solutions to reduce bullying behavior in students. This type of research is an experiment with a Pre-Experimental Design using the One Group Pretest Posttest Design model. The instrument used to determine student bullying is a bullying scale with good reliability and validity. Determination of the subject using the technique of Nonprobability Sampling Design by using Purposive Sampling. The subjects of this study were five students of class VII SMP Muhammadiyah 1 Prambanan, with very high categories of bullying behavior. Based on the study results, there is a difference between the level of student bullying behavior before and after being given a concise solution-focused counseling service.